Occupational therapists' perspectives and role with illness-induced trauma from medical conditions - Beyers, Camryn, author; Schmid, Arlene A., advisor; Weaver, Jennifer A., committee member; Currin-McCulloch, Jen, committee member (Colorado State University. Libraries, 2023)
Illness-induced trauma might cause a disruption in an individual's occupational performance. This study examined occupational therapy practitioner's perspectives and role in addressing illness-induced trauma in practice. In this explanatory sequential mixed methods design, twenty-four occupational therapists completed an online survey and ten occupational therapists participated in a semi-structured 1:1 interview. Survey questions asked about their knowledge of illness-induced trauma. Interview questions asked therapists about how they incorporate illness-induced trauma knowledge and trauma-informed care into their practice. Quantitative results showed that the majority of occupational therapists did not receive formal trauma-informed care training, 96% agreed that psychological trauma has a significant impact on rehabilitation outcomes, and 8% agreed that current guidelines for trauma-informed care adequately consider the needs of clients with illness-induced trauma. Qualitative results indicated three major themes: occupational therapy approaches, illness-induced trauma's effect on rehabilitation, and barriers to providing trauma-informed care. Findings suggest that occupational therapy practitioners have a unique perspective on addressing illness-induced trauma and their ability to practice trauma-informed care could support a client's ability to process and heal after a traumatic medical event.
Keywords: medical condition; trauma; illness-induced trauma; trauma-informed care; occupational therapy